Efficacy of a Micro-Prompting Technology in Reducing Support Needed by People With Severe Acquired Brain Injury in Activities of Daily Living: A Randomized Control Trial. Issue 5 (September 2018) - O'Neill, Brian; Best, Catherine; O'Neill, Lauren; Ramos, Sara D. S.; Gillespie, Alex
Abstract : Objective: To evaluate the effectiveness of an automated interactive prompting technology in supporting the morning routine of persons with acquired brain injury. The morning routine included maintaining personal hygiene and dressing. Setting: An inpatient neurorehabilitation hospital. Participants: Persons with acquired brain injury who required prompting when following their morning routine ( n = 24), but were not limited by physical disability or dysphasia, took part in the study. Participants (67% with traumatic brain injury) had impairment on indices of memory and executive function. Design: A randomized control trial evaluated the effect of an automated interactive micro-prompting device on the number of prompts by trained staff required for successful completion of the morning routine. Main Measures: Study-specific checklists assessed sequence performance, errors, and verbal prompts required over baseline, rehabilitation as usual, intervention, and return to baseline conditions. Results: The intervention significantly reduced the support required to complete the task compared with usual rehabilitation. Conclusions: Micro-prompting technology is an effective assistive technology for cognition, which reduces support needs in people with significant cognitive impairments.